Navigating Diversity and Inclusion in Veterinary Medicine - Amass, Sandra F.; Lowrie, Patricia M.; Davis, Kauline Cipriani; Greenhill, Lisa M. (Purdue University Press, 2013)
This book addresses the continued lack of the diversity in veterinary medicine, the least inclusive of all medical professions. Effective navigation of the complexity of diversity and inclusion in veterinary medicine requires clear enumeration, recognition, and understanding of key issues, challenges, and opportunities. In a nation with rapidly changing demographics, public needs and expectations of the veterinary profession will continue to evolve. A more diverse scientific workforce is required to feed the veterinary profession, not just for the purposed of equity, but as necessity for its sustainability and relevance.